Ptychopteridae -a family of flies (Diptera) new to the Neotropical Region and description of a new species - Hancock, E. Geoffrey; Marcos-Garcia, M-Angeles; Rotheray, Graham E. (Zootaxa, 2006)
A new species of Ptychoptera Meigen (Diptera: Ptychopteridae) is described from cloud forest in southern Mexico, representing the first definitive record of the family in the Neotropical Region.